THE IMPACT OF WORK RELATED VARIABLES ON LIBRARIANS’ ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION - Abdul Karim, Noor Harun (Malaysian Journal of Library and Information Science, 2010)
This study attempted to assess the impact of five (5) work related variables (role conflict, role clarity, job autonomy, job performance feedback and job involvement) on organizational commitment and job satisfaction among Malaysian university librarians. The study sought to address the following research questions: (a) do work related variables such as role conflict, role clarity, job autonomy, job performance feedback and job involvement correlate significantly as well as significantly predict the variation in organizational commitment and job satisfaction among university librarians in Malaysia; and (b) does this set of five (5) work related variables have a greater/lesser impact on organizational commitment as compared to job satisfaction or vice versa. A proportionate stratified random sampling technique was employed and questionnaires were distributed to 222 respondents comprising mainly of professionally trained library employees. A response rate of 63% was achieved resulting in 139 usable questionnaires that were returned. The findings of this study were based on the analysis of 139 usable questionnaires that were returned. The findings revealed that of the five (5) work related variables that were employed, all were found to be correlates of organizational commitment. Of these five correlates however, only three (3) were found to have statistically significant predictive relationship with organizational commitment: role clarity, job autonomy and job involvement Collectively these three (3) predictors account for 31.8% of the variance in organizational commitment. Of the five (5) work related variables that were employed to examine their relationship with job satisfaction, only four were found to correlate significantly with job satisfaction: role conflict, role clarity, job autonomy and job performance feedback. Of these 4 work correlates, only two (2) were found to significantly predict the variation in job satisfaction. Collectively these two variables (role conflict and role clarity) account for 16.3% of the variance in job satisfaction. Hence, the impact of work related variables was greater for organizational commitment (31.8% of the variance) than for job satisfaction (16.3% of the variance). Only role clarity was found to be a significant correlate as well as a significant predictor of organizational commitment as well as job satisfaction.